Foliar selenium biofortification of soybean: the potential for transformation of mineral selenium into organic forms - Mrština, Tomáš; Praus, Lukáš; Száková, Jiřina; Kaplan, Lukáš; Tlustoš, Pavel (Frontiers in Plant Science, 2024)
Selenium (Se) deficiency, stemming from malnutrition in humans and animals, has the potential to disrupt many vital physiological processes, particularly those reliant on specific selenoproteins. Agronomic biofortification of crops through the application of Se-containing sprays provides an efficient method to enhance the Se content in the harvested biomass. An optimal candidate for systematic enrichment, guaranteeing a broad trophic impact, must meet several criteria: (i) efficient accumulation of Se without compromising crop yield, (ii) effective conversion of mineral Se fertilizer into usable organically bound Se forms (Seorg), (iii) acceptance of a Se-enriched crop as livestock feed, and (iv), interest from the food processing industry in utilization of Se-enriched outputs. Hence, priority should be given to high-protein leafy crops, such as soybean. A three-year study in the Czech Republic was conducted to investigate the response of field-grown soybean plants to foliar application of Na2SeO4 solutions (0, 15, 40, and 100 g/ha Se); measured outcomes included crop yield, Se distribution in aboveground biomass, and the chemical speciation of Se in seeds.Seed yield was unaffected by applied SeO4 2-, with Se content reaching levels as high as 16.2 mg/kg. The relationship between SeO4 2-dose and Se content in seeds followed a linear regression model. Notably, the soybeans demonstrated an impressive 73% average recovery of Se in seeds. Selenomethionine was identified as the predominant species of Se in enzymatic hydrolysates of soybean, constituting up to 95% of Seorg in seeds. Minor Se species, such as selenocystine, selenite, and selenate, were also detected.The timing of Se spraying influenced both plant SeO4 2-biotransformation and total content in seeds, emphasizing the critical importance of optimizing the biofortification protocol. Future research should explore the economic viability, long-term ecological sustainability, and the broad nutritional implications of incorporating Se-enriched soybeans into food for humans and animals.